The origin of heterogeneous nanoparticle uptake by cells - Paul Rees (Nature Portfolio, 2019)
Cellular uptake of nanoparticles is highly variable between individual cells in a population. Here, the authors show that this heterogeneity is a result of varying numbers of nanoparticle-containing endosomes while the nanoparticle dose per endosome remains constant.